2022
DOI: 10.3390/ijms232012123
|View full text |Cite
|
Sign up to set email alerts
|

A Mitophagy-Related Gene Signature for Subtype Identification and Prognosis Prediction of Hepatocellular Carcinoma

Abstract: Globally, hepatocellular carcinoma (HCC) is the sixth most common cancer. In this study, the correlation between mitophagy and HCC prognosis was evaluated using data from The Cancer Genome Atlas (TCGA). Clinical and transcriptomic data of HCC patients were downloaded from TCGA dataset, and mitophagy-related gene (MRG) datasets were obtained from the Molecular Signature Database. Then, a consensus clustering analysis was performed to classify the patients into two clusters. Furthermore, tumor prognosis, clinico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 73 publications
0
12
0
Order By: Relevance
“…Most of these genes, except for DEDD and IL33, had also been included in different prognostic models of LIHC in previous studies. [35][36][37][38][39][40][41][42][43] The protein DEDD (death effector domain-containing protein) has been implicated in numerous physiological processes, including apoptosis. [44] Recent studies have suggested that DEDD could potentially serve as a valuable prognostic marker and therapeutic target for the treatment of cancer metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these genes, except for DEDD and IL33, had also been included in different prognostic models of LIHC in previous studies. [35][36][37][38][39][40][41][42][43] The protein DEDD (death effector domain-containing protein) has been implicated in numerous physiological processes, including apoptosis. [44] Recent studies have suggested that DEDD could potentially serve as a valuable prognostic marker and therapeutic target for the treatment of cancer metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…To date, research commonly focuses on speci c biological pathways, such as immunity, m6A methylation, and ferroptosis, to stratify HCC populations or construct prognostic survival models for patients (45)(46)(47). However, most of these studies were biased towards a single-omics and employed singular analysis methods such as ConsensusClustering, NMF clustering, or LASSO-Cox, which signi cantly limited the scope and adversely affected the accuracy of the nal outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Later, TCGA samples were classified into two subtypes using hierarchical clustering analysis based on the expression of mitophagy-related genes, and 16 DEGs were discovered in separate subtypes. A recent paper revealed that mitophagy-related biomarkers ( PGAM5, SQSTM1, ATG9A , and GABARAPL1 ) were survival-related genes of UM patients, which could be used to predict the survival of these patients ( Liu et al, 2022 ). Our results also showed the high expression of PGAM5 and SQSTM1 in the high immune-level and high-risk groups.…”
Section: Discussionmentioning
confidence: 99%
“…Although definitive functional changes and molecular mechanisms of mitophagy have not been completely elucidated, the expression levels of some mitophagy-related genes could serve as biomarkers for the diagnosis, prognosis, or therapy of some cancers ( Wang et al, 2021 ; Wang et al, 2022 ). A recent paper revealed that mitophagy is closely related to the clinical prognosis of patients with UM, and indicated that mitophagy-related biomarkers ( PGAM5, SQSTM1, ATG9A , and GABARAPL1 ) are survival-related genes of UM patients ( Liu et al, 2022 ). However, the mitophagy-related genes that cause pathogenesis, as well as their importance in the diagnosis, prognosis, and therapeutic interventions of UM, remain unclear.…”
Section: Introductionmentioning
confidence: 99%